2022
DOI: 10.1016/j.mtbio.2021.100195
|View full text |Cite
|
Sign up to set email alerts
|

Novel fusion peptides deliver exosomes to modify injectable thermo-sensitive hydrogels for bone regeneration

Abstract: Injectable thermo-sensitive hydrogels composed of small intestinal submucosa (SIS) with exosomes derived from bone marrow mesenchymal stem cells (BMSCs) are desired for bone regeneration. However, poor mechanical properties limit the clinical application of SIS hydrogels. Herein, the mechanical properties of SIS hydrogels incorporated with 3-(3,4-dihydroxyphenyl) propionic acid (CA) are assessed. The results show that the mechanical properties of SIS hydrogels are improved. In addition, the retention and stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 59 publications
(62 reference statements)
0
38
0
Order By: Relevance
“…To overcome this limitation, hydrogels are often modified by chemical, physical, and biological methods to prepare high-performance hydrogels with enhanced mechanical properties, stability, cell adhesion, and other properties [ 63 ]. Ma et al [ 67 ] used propionic acid (CA) with a catechol group to modify an injectable thermosensitive hydrogel through a covalent bond. The cross-linking network formed by the interaction between the catechol group of CA and the collagen molecules in hydrogels can effectively improve the mechanical properties of hydrogel [ 68 ].…”
Section: Application Of Msc-evs In Bone Defectsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this limitation, hydrogels are often modified by chemical, physical, and biological methods to prepare high-performance hydrogels with enhanced mechanical properties, stability, cell adhesion, and other properties [ 63 ]. Ma et al [ 67 ] used propionic acid (CA) with a catechol group to modify an injectable thermosensitive hydrogel through a covalent bond. The cross-linking network formed by the interaction between the catechol group of CA and the collagen molecules in hydrogels can effectively improve the mechanical properties of hydrogel [ 68 ].…”
Section: Application Of Msc-evs In Bone Defectsmentioning
confidence: 99%
“…The results showed that EVs could be effectively fixed to hydrogels through the interaction of protein domains on the cell membrane [ 29 ]. In another study, some scholars incorporated Exos into an injectable thermosensitive hydrogel by constructing fusion peptides, which also enhanced the retention of Exos and improved the biological activity of Exos [ 67 ]. The above results indicated that the addition of bioactive substances such as peptides can enhance the fixation and retention of EVs without impairing the structural integrity and biological activity of EVs.…”
Section: Application Of Msc-evs In Bone Defectsmentioning
confidence: 99%
“… Cao et al (2021) found that mature dendritic cell–derived exosomes enhance osteogenic differentiation of MSCs. Moreover, some studies have focused on regulating exosomes to increase their osteogenic activity, such as aptamer-functionalized exosomes, static magnetic field–treated exosomes, exosomes endowed with plasmids, genetic engineered exosomes, hypoxic environment-treated exosomes, hydrogel-assisted 3D cultured exosomes, and exosomes with fusion peptide ( Li et al, 2022 ; Luo et al, 2019 ; Ma et al, 2022 ; Shen et al, 2022 ; Wu et al, 2021 ; Yu et al, 2022 ; Zha et al, 2021 ). In general, the treatment of exosomes increases the osteogenic ability in the bone defect microenvironment, which is beneficial for bone defect repair.…”
Section: Applications Of Bone Engineering Scaffolds With Exosomes In ...mentioning
confidence: 99%
“…For example, Schwann cell–derived exosomes with porous titanium alloy can improve the effects of scaffolds in bone repair ( Wu et al, 2020 ). Ma et al (2022) reported that hydrogels combined with exosomes and fusion peptides can enhance the therapeutic effect and the retention of exosomes. Yang et al (2020) revealed that MSC-derived exosomes with injectable hydroxyapatite-embedded in situ cross-linked hyaluronic acid-alginate hydrogel can significantly enhance bone regeneration and retain the exosomes at the defect sites.…”
Section: Applications Of Bone Engineering Scaffolds With Exosomes In ...mentioning
confidence: 99%
“…[12][13][14] In view of their excellent biocompatibility, multiple bioactivity, hydrophilicity, and low immunogenicity, SIS has been widely applied as a cell culture matrix, surgical mesh, tissue engineering scaffold, guide tissue regeneration membrane, and wound dressing. [15][16][17][18][19][20] To treat chronic wounds that are difficult to heal via the individual use of SIS, various biochemical factors, including platelet-rich plasma, 21 silver nanoparticles (AgNPs), 22 mesenchymal stem cells, 23 and extracellular vesicles, 17 have been introduced into SIS hydrogel. Nevertheless, clinical translation of these strategies remains a challenge due to the high cost, complicated delivery strategy, and potential side effects (e.g., immunogenicity and tumorigenesis) of these encapsulated biochemical factors.…”
mentioning
confidence: 99%